2020
DOI: 10.1590/0100-3984.2019.0048
|View full text |Cite
|
Sign up to set email alerts
|

Spinopelvic sagittal balance: what does the radiologist need to know?

Abstract: Sagittal balance describes the optimal alignment of the spine in the sagittal plane, resulting from the interaction between the spine and lower limbs, via the pelvis. Understanding sagittal balance has gained importance, especially in the last decade, because sagittal imbalance correlates directly with disability and pain. Diseases that alter that balance cause sagittal malalignment and may trigger compensatory mechanisms. Certain radiographic parameters have been shown to be clinically relevant and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 51 publications
0
17
0
3
Order By: Relevance
“…Patients with lumbar degenerative disease are characterized by anterior sagittal imbalance, loss of LL, and increased PT ( 12 , 15 , 20 , 21 ). Ogon et al ( 16 ) found an association between anterior annulus fibrosus degeneration in all lumbar disc levels and hypolordosis of the lumbar spine, anterior translation of the trunk and posterior inclination of the pelvis in chronic low back pain using quantitative MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with lumbar degenerative disease are characterized by anterior sagittal imbalance, loss of LL, and increased PT ( 12 , 15 , 20 , 21 ). Ogon et al ( 16 ) found an association between anterior annulus fibrosus degeneration in all lumbar disc levels and hypolordosis of the lumbar spine, anterior translation of the trunk and posterior inclination of the pelvis in chronic low back pain using quantitative MRI.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies conducted in Brazil have highlighted the important role that imaging methods play in the evaluation of the musculoskeletal system (36)(37)(38)(39)(40) . In our study, the prevalence of imaging alterations in the CPN was high (36.8-39.4%), and the levels of interobserver and intraobserver agreement for these abnormalities were excellent (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…The published studies on functional outcome and SPA after spinal surgery have offered conflicting results. A number of studies have established a significant relationship between these parameters and outcomes, while others were unable to establish a relationship, even with positive outcomes, while these measurements were abnormal [2,3,7,10,12,[14][15][16]. This inconsistency may be due to other factors contributing to the outcome not being studied or due to the short follow-up procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The sacral slope (SS) is the angle between the horizontal line and the sacral plateau. The pelvic incidence is the sum of the pelvic tilting angles with the sacral slope (PI = PT+SS) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation